PENGARUH STRUKTUR MODAL TERHADAP NILAI PERUSAHAAN PADA PERUSAHAAN MANUFAKTUR GO PUBLIK (Studi Kasus Sektor Makanan Dan Minuman) - Putri, Julia; ", Ruzikna (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2016)
This study aims to identify and analyze the influence of Capital Structure of the Company Value. The period used in this study was 5 years, from 2010 to 2014. The data used in this research is secondary data, financial highlights (annual report) and performance summary. This study used purposive samplingmethodinorder tocollectthesample. Samples used are the 4 company of Food and Beverages. Analysis of data using simple linear regression analysisAnalysis of data using multiple linear regression analysis with SPSS 19.The results showed that the capital structure simultaneously not significantly affect the Company Value. The results of this study indicate that the variable X no affect variable Y.Keywords : Capital Structure, and Value of The Company.